2006
DOI: 10.1002/app.24787
|View full text |Cite
|
Sign up to set email alerts
|

Effect of different preparation routes on the structure and properties of rigid polyurethane‐layered silicate nanocomposites

Abstract: To identify the effect of reactive preparation on the structure and properties of rigid polyurethane (PU)-layered silicate nanocomposite, a range of nanocomposites were prepared by combining the various precursors in different sequences. The morphology of the samples was characterized by XRD and TEM. Tensile properties and dynamic mechanical thermal properties were measured. The reactions between the layered silicates and PU precursors were monitored via FTIR to gain an understanding of the participation of na… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2008
2008
2011
2011

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 16 publications
1
8
0
Order By: Relevance
“…Some papers on PU nanocomposite foams have been already reported [16][17][18][19][20][21][22][23][24] and only few deal with fire behaviour [20][21][22][23][24]. Seo et al [20] reported that the thermal stability and fire resistance properties of polyurethane foam/clay nanocomposite are enhanced when a higher degree of dispersion of filler is achieved (i.e.…”
Section: Introductionmentioning
confidence: 99%
“…Some papers on PU nanocomposite foams have been already reported [16][17][18][19][20][21][22][23][24] and only few deal with fire behaviour [20][21][22][23][24]. Seo et al [20] reported that the thermal stability and fire resistance properties of polyurethane foam/clay nanocomposite are enhanced when a higher degree of dispersion of filler is achieved (i.e.…”
Section: Introductionmentioning
confidence: 99%
“…AFM bolstered the conclusion of Li et al13 from SAXS that the mechanism of the phase segregation of urea domains was spinodal decomposition and the structure was bicontinuous. Polymer nanocomposites,14, 15 including polyurethane foam nanocomposites,16, 17 have attracted intense research interest in recent years and provide another useful field of application for AFM. One important issue for polymer nanocomposites is how to disperse well the nanoparticles and control their location in the foam structure (i.e., foam windows versus struts).…”
Section: Introductionmentioning
confidence: 99%
“…The reaction between layered silicates like as C30B and isocyanate has already been proved by several authors for different synthetic conditions 6,21,22 ; in this study, we will find out if the synthesis condition used here are such that this reaction takes place. For doing that, the evaluation of new groups' formation was carried on through Lambert-Beer's law.…”
Section: Resultsmentioning
confidence: 78%